Implementasi Program Pendaftaran Tanah Sistematis Lengkap, Kota Surabaya - Aprilliana Rahmani; Lilik Ekowanti (Public Administration Dept, Faculty of Social and Political Science, 2023)
The government has conducted the program of systematic and complete land registration (PTSL) in order to have a legal certainty guarantee and protection of human rights in owning land fairly and evenly, as well as to encourage the state economic growth generally and the community economy in Indonesia. The registration system is regulated by the Ministry of Agrarian and Spatial/ the head of BPN No.12 in the Year 2017 regarding the acceleration of systematic and complete land registration. The study examines the implementation of the PTSL program in Surabaya. This is a literature study that describes and analyzes by using policy implementation theory in George C. Edward III. The variables are communication, resources, disposition, and bureaucratic structure. The results explain that Surabaya has conducted a PTSL program which is begun from 2017 to recent years. The program continues to be carried out, so that the implementation of PTSL program in Surabaya has been done properly. The supporting factors in PTSL implementation re communication, i.e. the definite program, and bureaucratic structure in Standard Operating Procedure (SOP). Whereas, the inhibiting factors are the human resources, for example, the staff, budget, and the information. In addition, human resource is the most inhibiting factor in the process of PTSL implementation in Surabaya. The study also suggests that it is important to have management information system in land registration for supporting PTSL implementation.